2012
DOI: 10.1371/journal.pone.0033287
|View full text |Cite
|
Sign up to set email alerts
|

Blimp1 Activation by AP-1 in Human Lung Cancer Cells Promotes a Migratory Phenotype and Is Inhibited by the Lysyl Oxidase Propeptide

Abstract: B lymphocyte-induced maturation protein 1 (Blimp1) is a master regulator of B cell differentiation, and controls migration of primordial germ cells. Recently we observed aberrant Blimp1 expression in breast cancer cells resulting from an NF-κB RelB to Ras signaling pathway. In order to address the question of whether the unexpected expression of Blimp1 is seen in other epithelial-derived tumors, we selected lung cancers as they are frequently driven by Ras signaling. Blimp1 was detected in all five lung cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 66 publications
5
32
0
Order By: Relevance
“…6L). Our results are consistent with the link between Blimp1 and migratory ability of human lung and breast cancer cell lines in vitro (73,74). Blimp1 has not been described as a hypoxia/Hif target gene in normal cell types but hypoxia may also influence Blimp1 expression in those settings.…”
Section: Discussionsupporting
confidence: 90%
“…6L). Our results are consistent with the link between Blimp1 and migratory ability of human lung and breast cancer cell lines in vitro (73,74). Blimp1 has not been described as a hypoxia/Hif target gene in normal cell types but hypoxia may also influence Blimp1 expression in those settings.…”
Section: Discussionsupporting
confidence: 90%
“…Ectopic expression of LOX-PP reduced UXT protein levels by 40-50%. LOX-PP is a glycosylated protein that appears differentially modified in various cell types [Vora et al, 2010;Yu et al, 2012]. Consistently, ectopically expressed LOX-PP migrated at the expected position for unprocessed protein ($21 kDa) and also yielded multiple, glycosylated bands migrating more slowly, as seen previously.…”
Section: Lox-pp Causes a Relocalization Of Uxt And A Reduction In Itssupporting
confidence: 82%
“…In Ras ‐NIH 3T3 cells, expression of LOX‐PP, but not of the processed LOX enzyme, inhibited the transformed phenotype of the fibroblasts [Palamakumbura et al, ]. Similarly, ectopic PRO‐LOX or LOX‐PP expression in H1299 lung, PANC‐1 pancreatic and Her‐2/neu breast cancer cell lines reduced cell migration, growth in soft agar, invasive colony formation in Matrigel and the activation of extracellular signal‐regulated kinases (ERK) and Akt [Min et al, ; Wu et al, ; Yu et al, ]. Importantly, ectopic LOX‐PP expression or direct tumoral administration of recombinant protein reduced Her‐2‐driven breast tumor burden in a xenograft model [Min et al, ; Bais et al, ].…”
mentioning
confidence: 99%
“…Indeed, it has been shown that the downmodulation of Blimp1 in solid tumors leads to impaired cell migration both in non-small cell lung cancer and in ERα positive breast cancer cell lines, where Blimp1 represses the BMP5 protein 16, 18 .…”
Section: Discussionmentioning
confidence: 99%